A smart girl's guide. Worry : how to feel less stressed and have more fun - Woodburn, Judith, 1959-; Holyoke, Nancy (American Girl, 2016)
Offers advice for girls to deal with worrying and stress, letting them know that some worry is natural and giving them effective tips and techniques for taming fear and feeling more calm and confident.